Hierarchical Relationship of Negative Emotion Perception from Violent Video Games. (July 2017) - Lin, Hong-Wen; Luarn, Pin; Lin, Yu-Ling
Video games featuring violent contents have become more and more prevalent among children and teenagers. It is therefore imperative to ponder on questions such as 'Are violent video games dangerous digital games?' and 'What negative emotions do they trigger in gamers?' As such, this study aims to explore the negative emotions that violent video games trigger in gamers and determine the cause for each negative emotion. For the purpose of this research, Resident Evil, a violent video game, has been chosen as the focus. Taking the gamer's perspective, the study aims to explore and construct a thorough network structure (game triggered event—gamer's personal belief—feeling of negative emotions) of gamer's emotions, the structure of gamers' emotional cluster and the correlation and level of inter-influence between relevant factors. Results of the study reveal that the overall hierarchical value map (HVM) not only presents a comprehensive gamer emotional network structure but also offers a clear illustration of how key game activating events (enemies, stage mission, BOSS level monsters, horror atmosphere, third-person view) lead to the formation of gamers' personal beliefs of character death, high difficulty, trigger negative emotion, being frightened, enemy ambush and tough enemies, which ultimately lead to negative emotions such as fear, worry, anger, disgust and frustration on gamers' part. In addition, among the five gamer emotional clusters, the clusters of fear and anger had the heaviest influence on the gamers. The correlation between factors and influence showed different levels of significance.